2019
DOI: 10.3390/en12122432
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Capture for CO2 Emission Reduction in the Cement Industry in Germany

Abstract: The share of global CO2 emissions deriving from the cement industry is about 5%. More than 50% of these are process-related and cannot be avoided. This paper addresses the application of CO2 capture technology to the cement industry. Analyses focusing on post-combustion technology for cement plants are carried out on the basis of detailed model calculations. Different heat supply variants for the regeneration of loaded wash solution were investigated. CO2 avoidance costs are in a range of 77 to 115 EUR/tCO2. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 24 publications
(21 reference statements)
1
8
0
Order By: Relevance
“…). As shown by the previous work of Zhou et al [104], cases 1 and 2 (with energy import) presented the lowest equivalent energy consumption, 4.8 and 4.9 . Regarding the economic analysis, they concluded that the second case is the cheapest (80.8…”
Section: Chemical Absorption (Post-combustion Amine Scrubbing)supporting
confidence: 60%
See 1 more Smart Citation
“…). As shown by the previous work of Zhou et al [104], cases 1 and 2 (with energy import) presented the lowest equivalent energy consumption, 4.8 and 4.9 . Regarding the economic analysis, they concluded that the second case is the cheapest (80.8…”
Section: Chemical Absorption (Post-combustion Amine Scrubbing)supporting
confidence: 60%
“…Zhou et al [104] have done a comparative study between amine scrubbing (monoethanolamine) with CHP and amine scrubbing with imported steam and electricity. Assuming an 85% CO 2 capture rate, they concluded the cost of CO 2 avoided was comparable in both cases.…”
Section: Chemical Absorption (Post-combustion Amine Scrubbing)mentioning
confidence: 99%
“…The fraction of CO2 in flue gas from cement production, ranging from 15 to 30 mol%, is higher than the fraction found in flue gas from power plants [81,127]. Yet, CCUS solutions for power plants are not directly transferrable to cement production due to significant differences in equipment, processes and chemical/thermal reactions [128]. Reports have projected CCUS implementation in cement production plants to begin in 2030, and as such, a rigorous understanding of the technology and environmental impacts is required [129].…”
Section: Other Carbon Capture and Utilization Or Storage Opportunitiesmentioning
confidence: 99%
“…Cement production processes are energy-intensive and generate huge greenhouse emissions with the clinker energy intensity of about 3.4 GJ/t in 2018 [4] generating about 4% of the global CO 2 emission [8]. Strategies identified to reduce the emissions in cement production include improving heat recovery and energy efficiency [9][10][11], switching to low carbon source of energy [12], feedstock and material substitute [13][14][15], reducing the clinker-to-cement ratio [16] and advancing technology innovations such as carbon capture and storage [17,18]. Cement and concrete technology modelling and simulation have also been used to improve energy efficiency and usage [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%